2013
DOI: 10.1074/jbc.m113.517953
|View full text |Cite
|
Sign up to set email alerts
|

The Autoregulatory Feedback Loop of MicroRNA-21/Programmed Cell Death Protein 4/Activation Protein-1 (MiR-21/PDCD4/AP-1) as a Driving Force for Hepatic Fibrosis Development

Abstract: Background: MicroRNA-21 is important in hepatic fibrosis development, but the mechanism is unclear. Results: MicroRNA-21 is predominantly up-regulated in activated hepatic stellate cells and could form a double negative feedback loop that links fibrogenic machinery. Conclusion:The microRNA-21-mediated loop is a main driving force for hepatic fibrosis progression. Significance: It suggests a mechanism for how microRNA-21 contributes to hepatic fibrosis.Sustained activation of hepatic stellate cells (HSCs) leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 44 publications
3
91
1
Order By: Relevance
“…The upregulation of miR-21 is also observed in patients with idiopathic pulmonary fibrosis and in human fibrotic livers. 21,22 In the kidney, various studies have suggested that miR-21 is crucial in TGF-b-stimulated renal fibrosis. The levels of miR-21 could be increased Figure 4 Effects of SphK1/S1P and miR-21 on ECM proteins and EMT marker molecules expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of miR-21 is also observed in patients with idiopathic pulmonary fibrosis and in human fibrotic livers. 21,22 In the kidney, various studies have suggested that miR-21 is crucial in TGF-b-stimulated renal fibrosis. The levels of miR-21 could be increased Figure 4 Effects of SphK1/S1P and miR-21 on ECM proteins and EMT marker molecules expression.…”
Section: Discussionmentioning
confidence: 99%
“…13 The miR-21/programmed cell death protein 4/activation protein-1 (miR-21/PDCD4/AP-1) autoregulatory loop is one of the main driving forces for hepatic fibrosis and myocardial fibrosis. 21 Besides, MMP9/TIMP1, silencing metabolic pathways, and Smad 7 signaling might be also implicated in the miR-21-mediated fibrosis. 14,15 However, the specific mechanism and regulatory network that involved in the modulation of miR-21 to fibrotic dysfunction of kidney is not well defined and is the next focus point in our subsequent study.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Clinical expression data for PSCs have not been published yet, but for HSCs and liver fibrosis several investigations are available. The hepatic contents of miR-21 [27,28], miR-33a [29] and miR200b [30] were significantly increased in liver specimens from human patients with liver fibrosis as compared to normal patients. Upregulation was also identified for miR-199a-5p/199a-3p and miR-221/222 in hepatitis C induced liver fibrosis in a fibrosis progression-dependent manner.…”
Section: Clinical Relevance Of Mir In Cafmentioning
confidence: 92%
“…This appears to be based on a miR-21 feedback loop with these signaling pathways promoting fibrogenesis and the TGF-β signaling pathway underlying HSC activation. [28] MiR-145 is inducible by treatment with TGF-β leading to enhanced α-SMA expression in normal gastric fibroblasts and CAFs. [24] MiR-27a/b-transfected normal fibroblast showed α-SMA expression and increased production of TGF-β as typical characteristics of CAFs.…”
Section: Tgf-β Signalingmentioning
confidence: 99%
See 1 more Smart Citation